Improvements After Surgical Anesthesia in Elderly and Old Age Patients in the Intervention of the Hip Joint (Eurasian Research Bulletin, 2022)
Postoperative analgesia based on regional blockade of the lumbar plexus (0.1% solutions of naropine or marcaine) and the planned administration of NSAIDs (diclofenac, ketonal or xefocam) is a more effective method of analgesia after surgery in trauma patients of elderly and senile age. The use of low-concentration solutions of local anesthetics (0.1% naropin solution and 0.1% marcaine solution) makes it possible to obtain a complete sensory and minimal motor block, which contributes to the early activation of elderly and senile patients.